Why Europe grew rich and Asia did not : global economic divergenc e, 1600-1850 - Parthasarathi, Prasannan (Cambridge ; New York : Cambridge University Press, New York, 2011)
"Why Europe Grew Rich and Asia Did Not provides a striking new answe r to the classic question of why Europe industrialised from the late ei ghteenth century and Asia did not. Drawing significantly from the case of India, Prasannan Parthasarathi shows that in the seventeenth and eig hteenth centuries the advanced regions of Europe and Asia were more ali ke than different, both characterized by sophisticated and growing econ omies. Their subsequent divergence can be attributed to different compe titive and ecological pressures that in turn produced varied state poli cies and economic outcomes. This account breaks with conventional views , which hold that divergence occurred because Europe possessed superior markets, rationality, science or institutions. It offers instead a gro undbreaking rereading of global economic development that ranges from I ndia, Japan and China to Britain, France and the Ottoman Empire and fro m the textile and coal industries to the roles of science, technology a nd the state"--
Machine generated contents note: 1. Introduction; Part I. Setting th e Stage: Europe and Asia before Divergence: 2. India and the global eco nomy, 1600-1800; 3. Political institutions and economic life; Part II. The Divergence of Britain: 4. The European response to Indian cottons; 5. State and market: Britain, France, and the Ottoman Empire; 6. From c otton to coal; Part III. The Indian Path: 7. Science and technology in India, 1600-1800; 8. Industry in early nineteenth-century India; 9. Con clusion.
Keywords: Economic development -- Europe -- History; Economic development -- Asia -- History; Europe -- Economic conditions; Asia -- Economic conditions